Residence types and anemia determinants among female students at Universitas Negeri Semarang - Wulan Apriyani Hurlian; Syifa Qolbiyah Nasir (AcTion: Aceh Nutrition Journal, 2026)
The 2023 Indonesia Health Survey (IHS) data showed that the prevalence of anemia among adolescents aged 15–24 years in Indonesia is 15.5%, with a prevalence of 18% among adolescent girls, which, according to the WHO, is still considered a nutritional problem (>10%). Female university students aged 15–24 years are among the age groups at risk of developing anemia. This study aimed to investigate the association between residence type and factors influencing the risk of anemia among 105 female Universitas Negeri Semarang students. The study used quantitative cross-sectional methods, and the sample was determined using purposive sampling. The chi-square test results (p<0.05) showed a significant relationship between residence (p=0.001), food consumption (Fe p=0.000; protein p=0.000; vitamin C p=0.024), meal frequency (animal protein p=0.000; vegetable protein p= 0.000; vegetables p= 0.000; fruits p= 0.003), menstrual patterns (p=0.002), and knowledge about anemia (p=0.010) with the incidence of anemia. However, no significant association existed between dietary status and anemia (p=0.105) in female students of Universitas Negeri Semarang. The multivariate logistic regression test showed that residence type was the most dominant factor (OR=12.63). In conclusion, anemia prevention should focus on dietary patterns, knowledge, and living conditions as the main factors in the future